Salazar Slytherin as a Gothic Archetype: A Baldickian Interpretation of the Tyranny of the Past - Md. Alamin Sarker (ENJEL: English Journal of Education and Literature, 2026)
This paper aims to provide a detailed literary analysis of Salazar Slytherin, a character from J. K. Rowling’s Harry Potter book series (1997–2007), as a quintessential Gothic figure. It repositions the 10th-century founder of Hogwarts not just as a historical enemy in the Wizarding World, but as a key figure in the Gothic tradition. The study focuses on the ideas of critic Chris Baldick, who identifies several aspects of Gothic literature, such as the "tyranny of the past," the "stifling of the present," and the physical representation of these forces in confined or underground "dead-end" spaces. The paper argues that Slytherin represents the Byronic Villain. He is marked by an aristocratic ego and an obsessive belief in blood purity, reflecting the Gothic themes of ancestral decline and the "bad blood" in failing dynasties. By looking at Harry Potter and the Chamber of Secrets book and film through the perspective of Gothic architecture, this study shows how Slytherin’s underground lair acts as a "dead-end" crypt. This space physically embodies repressed secrets that burst into the modern world, disrupting the educational haven of the school. Furthermore, the analysis connects Slytherin’s character to the Dark Academia subculture. It explores how his status as the "Master of the Macabre," defined by Parseltongue and the control of the Basilisk, connects with the Gothic concept of the "Sublime," where fear and wonder meet. By comparing Slytherin to Eve Kosofsky Sedgwick’s ideas of "the unspeakable" and "the stifling of hopes," the article concludes that Slytherin is the main creator of the Gothic style at Hogwarts. His legacy is not a fixed history but a living "haunting." This shows that the Gothic nature of his character lies in his power to keep the ancient past in a harmful, overwhelming hold on the living.